A Comparision of Classical Holomorphic Dynamics and Holomorphic Semigroup Dynamics-I (The Nepali Mathematical Sciences Report, 2021)
In this paper, we compare existing results of the classical holomorphic dynamics with some of the existing results of holomorphic semigroup dynamics. We also prove some results of holomorphic semigroup dynamics, and we see whether there is a connection or contrast with classical one. Also, we see how far the results generalize, and what new phenomena appear.